VIRTUAL BLIND DATE (VBD) PANDEMI GENERATION - Qisthy Rabathy; Elly Komala; Kelvin Mohammad Yusron; Kamiliya Nabilah (Sean Institute, 2023)
Advances in increasingly sophisticated technology have created new cultures and phenomena. One of them is the increasingly massive use of virtual communication, especially the Covid-19 pandemic that is happening in the world today which limits direct human-to-human communication activities to avoid the spread and transmission of viruses, as if forcing humans to get used to and make virtual communication, this results in a new phenomenon, namely living a blind date or Virtual Blind Date (VDB). Virtual blind date can be interpreted as a meeting process between a man and a woman who have not been previously known which is done virtually, the goal is to be able to get a partner or lover. But apart from aiming to get a partner, another purpose of virtual blind dates is to meet someone who has never met before for the first time, with the intention of getting to know each other more deeply online, whose initial purpose is also to help someone find their soul mate. , also just for fun. This study is intended to describe how the processes and activities in Virtual Blind Date (VDB) activities. The research was conducted through the pre-field stage as well as the field work stage. This study uses qualitative methods, with the type of descriptive research.